Hidrops Fetalis - Norman Fahryl (Majority, 2020)
Fetal hydrops is a pathological condition defined as an excessive fluid accumulation and fetal serous cavities in two or more fetal compartements. These fetal hydrops are serious cases that are in the fetus and have a poor prognosis. The incidence of fetal hydrops is estimated to be 1 in 3000 pregnancies with prevalence tends to increase over time. The etiology of fetal hydrops can be divided into 2, within Immune Hydrops Fetalis (IHF) and Non-Immune Fetal Hydrops (NIHF). Previously, cases of fetal hydrops were dominated by Rhesus isoimmunization which resulted in severe fetal conditions. However, after the development of treatment and diagnosis of Rh isoimmunization, most cases of hydrops are caused by nonimmune conditions. One cause of nonimmune hydrops is haematologic disorders or anemia. This anemia itself has several causative factors, including genetic disorders, infections, vascular malformations, and hemorrhagic fetomaternal. Alpha thlassemia is a blood disorder that reduces the production of hemoglobin. The more severe type is known as hemoglobin Bart hydrops fetalis syndrome. Alpha thalassemia is the most common cause of fetal hydrops in Southeast Asian countries. This case is a 33 week pregnant woman with fetal hydrops accompanied by haematological abnormalities in the form of anemia. This case report highlights the link between anemia and fetal hydrops and treatment in cases of fetal hydrops.